2021
DOI: 10.52312/jdrs.2021.151
|View full text |Cite
|
Sign up to set email alerts
|

The external fixation can be a good alternative to plate-screw treatment in the surgical treatment of bilateral distal radius fractures: A retrospective cohort study

Abstract: Objectives: We aimed to compare the outcomes of two surgical treatment options, external fixator (EF) or open reduction and internal fixation (ORIF), in patients with bilateral distal radius fractures (DRFs). Patients and methods: Twenty-one patients (11 males 10 females; mean age: 40.0±16.0 years; range, 20 to 67 years) who underwent ORIF (n=10) or EF (n=11) due to bilateral DRF at between January 2011 and December 2019 were retrospectively analyzed. The Quick Disability of the Arm, Should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Therefore, the EF group had significantly lower surgery time and intraoperative blood loss than the VLP group (both p < 0.001), and avoided the trouble of second surgery to remove the implant. Dağtaş et al [ 10 ] compared the efficacy of EF and ORIF in the treatment of bilateral DRF and found that the wrist joint function in the EF group was better than that in the ORIF group during the first 2 months of treatment, making it a good choice for surgical treatment of bilateral DRF. Zhang et al [ 15 ] compared the efficacy of EF and ORIF in the treatment of DRF through a retrospective cohort study, and the results showed that external fixation can provide faster functional recovery and better functional outcomes than ORIF within 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the EF group had significantly lower surgery time and intraoperative blood loss than the VLP group (both p < 0.001), and avoided the trouble of second surgery to remove the implant. Dağtaş et al [ 10 ] compared the efficacy of EF and ORIF in the treatment of bilateral DRF and found that the wrist joint function in the EF group was better than that in the ORIF group during the first 2 months of treatment, making it a good choice for surgical treatment of bilateral DRF. Zhang et al [ 15 ] compared the efficacy of EF and ORIF in the treatment of DRF through a retrospective cohort study, and the results showed that external fixation can provide faster functional recovery and better functional outcomes than ORIF within 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…The main surgical treatment for DRF in adults is open reduction and internal fixation (ORIF) with a volar locking plate (VLP) being the most widely used due to its superior biomechanical properties [ 9 ]. External fixation (EF) is a traditional and commonly used treatment method for DRF due to its mature technique and ease of application, and many surgeons have applied it in the treatment of DRF [ 10 ]. However, there is still no consensus on the optimal surgical treatment for DRF [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Seven articles compared volar plating with dorsal plating [1,8,24,29,30,34,53], eight compared volar plating with casting [2,5,10,18,29,43,44,54], 15 compared volar plating with external fixation [3,7,11,12,15,17,21,23,36,39,40,42,50,52,55], and six compared volar plating with K-wire fixation [9,27,32,35,51,56]. Study characteristics, including the number of patients in each treatment group, the sensitivity analyses implemented (if any), and RRs for total and major complications were recorded (Table 1).…”
Section: Study Retrieval and Characteristicsmentioning
confidence: 99%
“…The prognosis of patients with good joint function recovery is crucial for improving the quality of life of patients. [ 1 ] Belonging to the transforming growth factor-alpha (TGF-β) family, bone morphogenetic protein-7 (BMP-7) has been verified to promote the rapid recovery of bone injuries in clinic. [ 2 ] Thromboxane A2 (TXA2) is a vasoactive factor.…”
Section: Introductionmentioning
confidence: 99%